Fabrication of newspaper-based nickel cobaltite nanosheet supercapacitor - Lee, Wei Chin (2018)
Supercapacitors are believed to the up-and-coming energy storage device which bridges the gap of traditional supercapacitor and batteries. The market of wearable electronics has growing rapidly which is boosting the improvement of flexible supercapacitors. Laboratory filter paper as a form of substrate has been used for supercapacitor in literature. Newspaper which is lightweight, cheaper, the highly recyclable will be a suitable candidate to replace filter paper. As newspaper is an insulator, electroless plating of nickel will be done on the paper to convert it into a conductive substrate. Nickel cobaltite which has good pseudocapacitive properties is electrodeposited onto the nickel coated newspaper. Electrochemical performance of the fabricated newspaper is characterized by key parameters such as cyclic stability, specific capacitance and rate capability. The nickel coated newspaper that has been electrodeposited with a presence of surfactant has shown better results compared to the newspapers without surfactant added. Annealing also increase the capacitance retention after 3000 cycles of the sample compared to chemical oxidation. The specific capacitance of the newspaper that has been added with surfactant and annealed is 1114.67mF/cm2 and the equivalent series resistance is ~1.3 Ω. The capacitance retention after 3000 cycles was 64.32%. Newspaper can be concluded to be a suitable alternative to filter paper as a substrate for supercapacitor.